(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper aims to set a guide for marketing professionals, in order to allow practitioners to select between post and e-mail as direct marketing tools. Despite the growing relevance of direct mail in its different formats, existing literature (professionaland scientific) does not provide clear criteria to select between these two options.Lack of clear criteria results into heterogeneous marketing practices. A choice between these tools is more based on habits, personal preferences or previous experiences. Key variables –based analysis usually does not guide the decision. In order to help marketing practitioners to choose between postal mail and email, this paper applies a conceptual model. This model is then combined with company priorities. Real situations can be replicated this way, allowing for proposition formulation. These propositions will tell us which one of the two tools is the most suited one for a specific situation. Finally, the article identifies factors that cannot by them selves guide the selection between postal mail and e-mail.